Explaining the Effects of Political Islam and Preacher toward Prabowo’s Electoral Dominance: Evidence from Pekanbaru and Kampar - Saputra, Andhik Beni; Setiawan, Azhari; Herpina, Hesti (UI Scholars Hub, 2021)
political affairs. The literature on voter behavior in many countries shows that religious leaders have critical roles in directing the political orientation and behavior of their followers. This article aims to examine the influence of Ustadz Abdul Somad (UAS) toward a significant increase of Prabowo’s vote share in the 2019 presidential election in Riau Province. Although Prabowo lost to Jokowi with a large margin in the last election, he was able to claim electoral victory in 13 out of 34 provinces—one of them is Riau. We assume that Prabowo gained the electoral advantage over his rival in Riau due to electoral support from UAS that ultimately gave significant effect toward a sharp increase for his votes compared to the 2014 election. We apply the quantitative method to examine the phenomenon. The data are mainly collected through a survey conducted in the two most populous regions in Riau—Pekanbaru and Kampar Regency. Our study confirms that UAS has a significant effect on Muslim voters’ orientation and behavior to vote for Prabowo in the last presidential election. Other findings in this study are also in line with previous studies suggesting a critical influence of religion, particularly Islam, in driving Muslim’s political behavior. The contribution of our study is to enrich the literature on voter behavior in Indonesian politics by examining the influence of political support from a popular preacher—UAS—on the distribution of electoral support for presidential candidates in the 2019 election. This is further strengthened by the presence and role of ulama figures who give their support to each presidential candidate in the political contestation in 2019.